Acute endovascular treatment delivery to ischemic stroke patients transferred within a telestroke network: a retrospective observational study. Issue 5 (July 2017) - Barlinn, Jessica; Gerber, Johannes; Barlinn, Kristian; Pallesen, Lars-Peder; Siepmann, Timo; Zerna, Charlotte; Wojciechowski, Claudia; Puetz, Volker; von Kummer, Rüdiger; Reichmann, Heinz; Linn, Jennifer; Bodechtel, Ulf
Background: Five randomized controlled trials recently demonstrated efficacy of endovascular treatment in acute ischemic stroke. Telestroke networks can improve stroke care in rural areas but their role in patients undergoing endovascular treatment is unknown. Aim: We compared clinical outcomes of endovascular treatment between anterior circulation stroke patients transferred after teleconsultation and those directly admitted to a tertiary stroke center. Methods: Data derived from consecutive patients with intracranial large vessel occlusion who underwent endovascular treatment from January 2010 to December 2014 at our tertiary stroke center. We compared baseline characteristics, onset-to-treatment times, symptomatic intracranial hemorrhage, in-hospital mortality, reperfusion (modified Treatment in Cerebral Infarction 2b/3), and favorable functional outcome (modified Rankin scale ≤ 2) at discharge between patients transferred from spoke hospitals and those directly admitted. Results: We studied 151 patients who underwent emergent endovascular treatment for anterior circulation stroke: median age 70 years (interquartile range, 62–75); 55% men; median National Institutes of Health Stroke Scale score 15 (12–20). Of these, 48 (31.8%) patients were transferred after teleconsultation and 103 (68.2%) were primarily admitted to our emergency department. Transferred patients were younger (p = 0.020), received more frequently intravenous tissue plasminogen activator (p = 0.008), had prolonged time from stroke onset to endovascular treatment initiation (p < 0.0001) and tended to have lower rates of symptomatic intracranial hemorrhage (4.2% vs. 11.7%; p = 0.227) and mortality (8.3% vs. 22.6%; p = 0.041) than directly admitted patients. Similar rates of reperfusion (56.2% vs. 61.2%; p = 0.567) and favorable functional outcome (18.8% vs. 13.7%; p = 0.470) were observed in telestroke patients and those who were directly admitted. Conclusions: Telestroke networks may enable delivery of endovascular treatment to selected ischemic stroke patients transferred from remote hospitals that is equitable to patients admitted directly to tertiary hospitals.